Self-assembly and controllable synthesis of graphene hydrogel adsorbents with enhanced removal of ciprofloxacin from aqueous solutions. Issue 87 (5th September 2016) - Ma, Jie; Sun, Yiran; Yu, Fei
Abstract : A convenient and efficient approach was applied for the assembly of graphene hydrogel (GH) adsorbents for the enhanced removal of ciprofloxacin (CIP) from an aqueous solution. Abstract : A convenient and efficient approach was applied for the assembly of graphene hydrogel (GH) adsorbents for the enhanced removal of ciprofloxacin (CIP) from an aqueous solution. Different structures and adsorption properties of the GH were obtained by adjusting the controlling factors, including the reductants, temperature, pH, and capping reagents. The physicochemical properties of the GH were systematically characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and the Brunauer–Emmett–Teller (BET) method. The reductant, higher temperature and lower pH enhance the structural properties but reduce the adsorption performance. The capping reagent improves both structural and adsorption properties. The structural properties of the GH, including the specific surface area, adsorption sites, and hydrophobicity, are crucial for the adsorption performance of CIP onto GH. The adsorption mechanism is attributed to hydrogen bonding, π–π electron donor–acceptor (EDA) interaction and other interactions between CIP and GH. The best adsorption capacity in this paper can reach 312 mg g −1 . These findings provide a reference for adjusting the structure and adsorption properties of GH, which could provide practical applications by controlling the assembly process and parameters.